2019
DOI: 10.1097/sla.0000000000003550
|View full text |Cite
|
Sign up to set email alerts
|

500 Minimally Invasive Robotic Pancreatoduodenectomies

Abstract: Objectives: This study aims to present the outcomes of our decade-long experience of robotic pancreatoduodenectomy and provide insights into successful program implementation. Background: Despite significant improvement in mortality over the past 30 years, morbidity following open pancreatoduodenectomy remains high. We implemented a minimally invasive pancreatic surgery program based on the robotic platform as one potential method of improving outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 50 publications
(126 reference statements)
7
100
0
1
Order By: Relevance
“…The majority of data regarding robotic training and building a comprehensive surgical oncology robotic center 40 has come from the University of Pittsburgh, which recently reported their experience with 500 robotic pancreaticoduodenectomies (RPD) 41 . In addition, the development of Fundamentals of Robotic Surgery which includes 25 outcomes measures required by a surgeon to safely perform robotic surgery regardless of specialty has been proposed.…”
Section: Training Curricula For Minimally Invasive Pancreas Surgerymentioning
confidence: 99%
“…The majority of data regarding robotic training and building a comprehensive surgical oncology robotic center 40 has come from the University of Pittsburgh, which recently reported their experience with 500 robotic pancreaticoduodenectomies (RPD) 41 . In addition, the development of Fundamentals of Robotic Surgery which includes 25 outcomes measures required by a surgeon to safely perform robotic surgery regardless of specialty has been proposed.…”
Section: Training Curricula For Minimally Invasive Pancreas Surgerymentioning
confidence: 99%
“…Die Arbeitsgruppe in Pittsburgh veröffentlichte vor Kurzem mit 500 Eingriffen die bislang größte Serie robotisch assistierter PD. Hier lagen die Mortalität bei 3,1 %, die Morbidität bei 24 %, die Reoperationsrate bei 26 % und die Konversionsrate bei 26 % [20].…”
Section: Qualitätssicherungunclassified
“…Are there contraindications or is RPD safe/superior for all indications? (38). Second, is there a minimum annual volume for safe implementation of RPD.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the importance of specific training programs for RPD to shorting the learning curve and minimize or even exclude any patient risk during this phase. This review describes the training programs for RPD and other robot pancreas surgery found in the literature (4, 1618).…”
Section: Introductionmentioning
confidence: 99%